Non-trivial avalanches triggered by shear banding in compression of metallic glass foams - Lin, H.; Lu, Chunsheng; Wang, H.Y.; Dai, L.H. (ROYAL SOC, 2020)
Ductile metallic glass foams (DMGFs) are a new type of structural material with a perfect combination of high strength and toughness. Owing to their disordered atomic-scale microstructures and randomly distributed macroscopic voids, the compressive deformation of DMGFs proceeds through multiple nanoscale shear bands accompanied by local fracture of cellular structures, which induces avalanche-like intermittences in stress–strain curves. In this paper, we present a statistical analysis, including distributions of avalanche size, energy dissipation, waiting times and aftershock sequence, on such a complex dynamic process, which is dominated by shear banding. After eliminating the influence of structural disorder, we demonstrate that, in contrast to the mean-field results of their brittle counterparts, scaling laws in DMGFs are characterized by different exponents. It is shown that the occurrence of non-trivial scaling behaviours is attributed to the localized plastic yielding, which effectively prevents the system from building up a long-range correlation. This accounts for the high structural stability and energy absorption performance of DMGFs. Furthermore, our results suggest that such shear banding dynamics introduce an additional characteristic time scale, which leads to a universal gamma distribution of waiting times.